"I cannot feel your print". How military strategic knowledge managers respond to digitalization. Issue 2 (23rd August 2021) - Heltberg, Therese
Abstract : Purpose: The purpose of this paper is to explore how military strategic knowledge managers consider and respond to digitalization of operational processes in their revision of military knowledge management technologies. The research question is: which strategic considerations and professional concerns impact decisions about how far digitalization should be incorporated into Army planning doctrine? Design/methodology/approach: The paper presents material from a qualitative research study which observed the process of revising Danish Army Field Manual III. The empirical data include 12 in-depth interviews as well as documents related to the revision process. Data were analysed using a thematic approach. Findings: The paper identifies and discusses strategic dilemmas arising from incorporating digitalization into planning doctrine. Two major areas of concern are addressed. The first involves considerations about the extent of digitalization, including concerns about risk and issues of timing regarding choices of specific digital solutions. The second involves potential limits of digitalization in relation to military notions of the role and identity of the commander. The article suggests that digitalization may impact on professional roles and identities and that strategic knowledge management developers need to be cognizant of this. Originality/value: The paper contributes to the literature in two ways. First, the paper draws attention to the notions of risk and timing in relation to strategic decisions on how far knowledge management technologies should make use of possibilities brought about by digitalization. Second, the paper provides insight into how digitalization may profoundly alter professional roles and identities.